The Effects of Krill Oil on mTOR Signaling and Resistance Exercise: A Pilot Study. (26th April 2018) - Georges, John; Sharp, Matthew H.; Lowery, Ryan P.; Wilson, Jacob M.; Purpura, Martin; Hornberger, Troy A.; Harding, Flint; Johnson, James H.; Peele, David M.; Jäger, Ralf
Abstract : Introduction . Krill oil supplementation has been shown to improve postexercise immune function; however, its effect on muscle hypertrophy is currently unknown. Therefore, the aim of present study was to investigate the ability of krill oil to stimulate mTOR signaling and its ability to augment resistancetraining-inducedchanges in body composition and performance. Methods . C2 C12 myoblasts cells were stimulated with krill oil orsoy-derivedphosphatidylcholine (S-PC), and then, the ratio of P-p70-389to total p70 was used as readout for mTOR signaling. Indouble-blind, placebo-controlledstudy, resistance trained subjects consumed either 3 g krill oil daily or placebo, and each took part in an 8-week periodized resistance training program. Body composition, maximal strength, peak power, and rate of perceived recovery were assessed collectively at the end of weeks 0 and 8. In addition, safety parameters (comprehensive metabolic panel (CMP), complete blood count (CBC), and urine analysis (UA)) and cognitive performance were measured pre- and posttesting. Results . Krill oil significantly stimulated mTOR signaling in comparison to S-PC and control. No differences for markers on the CMP, CBC, or UA were observed. Krill oil significantly increased lean body mass from baseline (p = 0.021, 1.4 kg, +2.1%); however, there were no statistically significant differences between groups for any measures taken. Conclusion . Krill oil activates mTOR signaling. Krill oil supplementation in athletes is safe, and its effect on resistance exercise deserves further research.